Behaviour spouses as marriage satisfaction factor - Alla Kovalenko; Eugenia Balyka (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
Levels of marriage satisfaction in family pairs are analyzed. Differences in life values of men and women are recognized. The hypothesis about the connection of marriage satisfaction and life values marriage partners have is confirmed.
Keywords: marriage satisfaction; life values; material values; spiritual values; family environment scale